On the response of a system with bound states of particles to the perturbation by the external electromagnetic field - Slyusarenko, Yu.V.; Sotnikov, A.G. (Condensed Matter Physics, 2006)
The response of the system, consisting of two types of opposite-charged fermions and their bound states
(hydrogen-like atoms), to the perturbation by the external electromagnetic field in low particle kinetic energies
region is studied. Investigations are based on using a new formulation of the second quantization method that
includes a capability of forming the particle bound states [1]. Expressions for Green functions that describe
the system response to the external electromagnetic field and take into account the presence of particle
bound states (atoms) are found. Macroscopic parameters of the system, such as conductivity, permittivity
and magnetic permeability in terms of these Green functions are found. As an example, the perturbation of
the ideal hydrogen-like plasma by the external electromagnetic field in low temperature region is considered.
Expressions for the values are found that describe the ideal gas of hydrogen-like atoms Bose-condensate
response to the external electromagnetic field. Дослiджується вiдгук системи, у якiй присутнi два типи фермiонiв з протилежними зарядами та їх
зв’язанi стани (атоми водневого типу), на збурення зовнiшнiм електромагнiтним полем у областi
малих кiнетичних енергiй частинок. Дослiдження базуються на використаннi нового формулювання
методу вторинного квантування, що включає можливiсть утворення зв’язаних станiв частинок [1].
Знайдено вирази для функцiй Грiна, що описують вiдгук системи на зовнiшнє електромагнiтне поле та враховують присутнiсть зв’язаних станiв частинок (атомiв). За допомогою цих функцiй Грiна
знайдено макроскопiчнi параметри системи, такi як провiднiсть, дiелектрична та магнiтна проникнiсть. Як приклад розглянуто збурення iдеальної водневоподiбної плазми зовнiшнiм електромагнiтним полем у низькотемпературному дiапазонi. Знайдено вирази для величин, що описують вiдгук
бозе-конденсату iдеального газу водневоподiбних атомiв на зовнiшнє електромагнiтне поле.